Compact Stacked-Patch Antenna for Directional Modulation in Azimuth and Elevation Planes - Zandamela, Abel Abdul; Marchetti, Nicola; Narbudowicz, Adam (IEEE, 2022)
This work proposes a compact stacked-patch antenna capable of beamsteering in the vertical and horizontal directions. These characteristics are studied to realize directional modulation (DM) schemes in the vertical and horizontal planes, using a structure of 0.56λ diameter. The design offers a unidirectional beamsteering across the entire xy-plane, with a scanning range of 118° and 112° in the xz and yz-planes, respectively. A peak realized gain of 6.75 dBi is achieved, with an isolation better than 15 dB at the center frequency of 2.4 GHz. directional modulation performance shows a beamwidth with Bit Error Rate (BER) < 10−2 of 33° in the horizontal plane, and 50° for the elevation planes. This performance is proposed to improve the secrecy and privacy of data transmission in the growing field of small Internet of Things (IoT) technology.
2022 IEEE International Symposium on Antennas and Propagation and USNC-URSI Radio Science Meeting (APS/URSI)
PUBLISHED
Denver, United States
Keywords: Physical Layer Security, Compact Antennas, MIMO Antennas; Telecommunications